Comparative genomics reveals Cyclospora cayetanensis possesses coccidia-like metabolism and invasion components but unique surface antigens. (December 2016) - Liu, Shiyou; Wang, Lin; Zheng, Huajun; Xu, Zhixiao; Roellig, Dawn; Li, Na; Frace, Michael; Tang, Kevin; Arrowood, Michael; Moss, Delynn; Zhang, Longxian; Feng, Yaoyu; et al.
Abstract Background Cyclospora cayetanensis is an apicomplexan that causes diarrhea in humans. The investigation of foodborne outbreaks of cyclosporiasis has been hampered by a lack of genetic data and poor understanding of pathogen biology. In this study we sequenced the genome ofC. cayetanensis and inferred its metabolism and invasion components based on comparative genomic analysis. Results The genome organization, metabolic capabilities and potential invasion mechanism ofC. cayetanensis are very similar to those ofEimeria tenella . Propanoyl-CoA degradation, GPI anchor biosynthesis, andN -glycosylation are some apparent metabolic differences betweenC. cayetanensis andE. tenella . UnlikeEimeria spp., there are no active LTR-retrotransposons identified inC. cayetanensis . The similar repertoire of host cell invasion-related proteins possessed by all coccidia suggests thatC. cayetanensis has an invasion process similar to the one inT. gondii andE. tenella . However, the significant reduction in the number of identifiable rhoptry protein kinases, phosphatases and serine protease inhibitors indicates that monoxenous coccidia, especiallyC. cayetanensis, have limited capabilities or use a different system to regulate host cell nuclear activities.C. cayetanensis does not possess any cluster of genes encoding the TA4-type SAG surface antigens seen inE. tenella, and may use a different family of surface antigens in initial host cell interactions. Conclusions Our findings indicate thatC. cayetanensis possesses coccidia-like metabolism and invasion components but unique surface antigens. Amino acid metabolism and post-translation modifications of proteins are some major differences betweenC. cayetanensis and other apicomplexans. The whole genome sequence data ofC. cayetanensis improve our understanding of the biology and evolution of this major foodborne pathogen and facilitate the development of intervention measures and advanced diagnostic tools.